Peluang dan Tantangan Program Studi Pendidikan Nonformal dalam Pembangunan Masyarakat Pasca Implementasi UU Nomor 23 Tahun 2014 tentang Pemerintah Daerah di Era Ekonomi Digital - Muhammad Ivan (Kementerian Koordinator Bidang Pembangunan Manusia dan Kebudayaan Republik Indonesia, 2021)
Law Number 23 of 2014 concerning Regional Government opens up space for Non-Formal Education to play a more specific role in accommodating residents who have not completed formal education. In the midst of the Industrial Revolution 4.0 era, it has triggered a shift in the HR development system both in Formal, Informal, and Non-Formal Education to adapt in the digital era. Poverty alleviation which is one of the National Priority goals in the Government's 2019 Work Plan encourages the PNF Study Program to have a human resource development system, especially human resources that is not accommodated by formal education, working class communities, women, out-of-school children, and ethnic minorities and excluded social classes. The digital economy offers solutions with new job specifications and eliminates 50 million job opportunities in the near future. This study uses a qualitative approach and uses the literature method. The results of the study indicate that the PNF Study Program has the opportunity to become a forum for thinking by conducting research to identify the needs of the community and the growing trend of the digital economy. The research findings show that the PNF Study Program can be a think tank to produce useful research for ministries and institutions. The conclusion in this study shows that in terms of poverty alleviation the role of the PNF Study Program is in line with the National Priorities in the Government Work Plan which aims to improve the quality of community development.